2014
DOI: 10.1038/nchembio.1495
|View full text |Cite
|
Sign up to set email alerts
|

Golgi sorting regulates organization and activity of GPI proteins at apical membranes

Abstract: Here, we combined classical biochemistry with novel biophysical approaches to study with high spatial and temporal resolution the organization of GPI-anchored proteins (GPI-APs) at the plasma membrane of polarized epithelial cells. We show that in polarized MDCK cells, following sorting in the Golgi, each GPI-AP reaches the apical surface in homo-clusters. Golgi-derived homo-clusters are required for their subsequent plasma membrane organization into cholesterol-dependent hetero-clusters. By contrast, in non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
94
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(104 citation statements)
references
References 53 publications
4
94
2
Order By: Relevance
“…Oligomerization has been proposed to facilitate GPI-AP segregation from other secretory proteins and to promote the coalescence of small lipid domains into larger and more stable domains that would favor vesicle budding from the TGN ( 68 ). In polarized epithelial cells, the oligomerization-based sorting mechanism of GPI-APs in the Golgi acquires a tremendous physiological relevance because it regulates both their organization and function at the apical membrane ( 75 ). N-glycosylation has been shown to be additionally required for apical delivery of GPI-APs, as well as other apically-targeted glycoproteins, suggesting an involvement of a lectin receptor-based mechanism ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oligomerization has been proposed to facilitate GPI-AP segregation from other secretory proteins and to promote the coalescence of small lipid domains into larger and more stable domains that would favor vesicle budding from the TGN ( 68 ). In polarized epithelial cells, the oligomerization-based sorting mechanism of GPI-APs in the Golgi acquires a tremendous physiological relevance because it regulates both their organization and function at the apical membrane ( 75 ). N-glycosylation has been shown to be additionally required for apical delivery of GPI-APs, as well as other apically-targeted glycoproteins, suggesting an involvement of a lectin receptor-based mechanism ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Golgi homoclustering not only mediates apical sorting of GPI‐APs but it is also required for their subsequent organization at the apical PM . Specifically, it has been shown that newly arrived homoclusters coalesce in heteroclusters (containing at least two different GPI‐AP species) that are sensitive to cholesterol depletion (Fig. ).…”
Section: Clustering Of Gpi‐aps In the Golgi Regulates Apical Sortingmentioning
confidence: 99%
“…Conversely, once formed, GPI‐AP homoclusters become insensitive to cholesterol depletion. Current data suggest that both protein–lipid and protein–protein interactions are involved in the formation and stabilization of GPI‐AP clusters . Although the biochemical nature of the interactions that determine apical GPI‐AP clustering prior to their apical sorting are not totally clear, the bulk of the evidence point out on the integrated action of the protein ectodomain and the GPI anchor together with the requirement of a favourable lipid environment (i.e., need of threshold levels of cholesterol in the Golgi membranes).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although fibroblasts and polarized epithelial cells might share this requirement, we have recently shown that the plasma membrane organization of GPI-APs is considerably different between fibroblasts and epithelial cells. Furthermore, we find that, in polarized epithelial cells, the oligomerization-based sorting mechanism of GPI-APs in the Golgi appears to regulate both their organization and function at the apical membrane (Paladino et al, 2014).…”
Section: Mechanism Of Oligomerizationmentioning
confidence: 97%